Os tribunais arbitrais e o conceito de órgão jurisdicional para efeitos de aplicação do artigo 267º TFUE - Figueiredo, Ana Rita Faial (2018)
Unaccompanied asylum seeking minors leaving their countries of origins face a serious of challenges and dangerous situations on the way to their countries of destination. However, even when they arrive at safe countries they still face a number of violations of human rights, perpetuated by the receiving states. This thesis approaches this matter in the European Union, focusing on the main international human rights instrument protecting children, the Convention on the Rights of the Child, and the central European directive on the reception of asylum seekers, alongside other relevant binding and non-binding legal documents, doctrine and jurisprudence. Enshrined in the Convention is the best interest of the child principle, a controversial and essential part of it, which this dissertation will reflect upon through the detention of unaccompanied asylum seeking minors, a vulnerable group, in European Union territory. In order to do this, the thesis analyses the different stages that lead and affect the detention of minors - arrival procedures, asylum granting processes and judicial guarantees. Finally, it seeks to reflect on the act of the detention of unaccompanied asylum seeking minors itself by its assessing its legality concerning the principle of last resort and the principle of minimum time of detention as possible. As such, this thesis aims to shine light on the numerous violations of human rights that unaccompanied asylum seeking minors often suffer upon arrival in Europe and how their illegality is proven through a series of international, regional and national legally binding articles and principles, even if these acts are continuously perpetuated and states attempt to justify them.